KARAKTERISTIK BATUBARA FORMASI WARUKIN DALAM PEMBENTUKAN CBM DI WILAYAH KABUPATEN TANAH BUMBU, PROVINSI KALIMANTAN SELATAN - Denny Suwanda Djohor; Harry Pramudito (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2017)
Increasing world oil prices have a huge impact on national energy needs. Indonesia's economic growth requires the development of alternative energy sources based on 10 basin assessments in Indonesia, coal methane gas potential is estimated to reach 337 TCF of gas in place (Advanced Resources International, inc). The research location is located in the Basin of Asam-Asam,South Kalimantan. Targeted research on the Miocene Warukin Formation. The data used to evaluate Coal Methane Gas potential include surface geology data and coal sample analysis, as well as characteristics of regional anomaly bouger for South Kalimantan. The development of cleats and fractures in coal at the observation site can be classified into high-intensity vitamite-rich coal categories. Coal Warukin Formation has an average Rv value = 0.56% with standard deviation 0.02%. and is ranked in sub-bituminous coal rank. While for other Warukin Formation coal has an average Rv value = 0.58% and entered in rank (bit) bituminous coal with type of methane gas is the type of bio & thermogenic gas mixture. When viewed from the thick layer of coal and gas type, the Warukin Formation coal in the location of research is quite interesting when included in the coal resources of economical coal methane gas.